How changes in oil prices affect the macroeconomy - Brian DePratto; Carlos De Resende; Philipp Maier (Bank of Canada, 2009)
We estimate a New Keynesian general-equilibrium open economy model to examine how changes in oil prices affect the macroeconomy. Our model allows oil price changes to be transmitted through temporary demand and supply channels (affecting the output gap), as well as through persistent supply side effects (affecting trend growth). We estimate this model for Canada, the United Kingdom, and the United States over the period 1971-2008, and find that it matches the data very well in terms of first and second moments. We conclude that (i) energy prices affect the economy primarily through the supply side, whereas we do not find substantial demand-side effects; (ii) higher oil prices have temporary negative effects on both the output gap and on trend growth, which translates into a permanent reduction in the level of potential and actual output. Also, results for the United States indicate that oil supply shocks have more persistent negative effects on trend growth than oil demand shocks. These effects are statistically significant; however, our simulations also indicate that the effects are economically small.
Keywords: F41; Q43; 330; Economic models; Interest rates; Transmission of monetary policy; Productivity; Potential output; Mineralölpreisschock; Makroökonomischer Einfluss; Zins; Produktivität; Gesamtwirtschaftliche Produktion; Geldpolitik; USA; Kanada; Großbritannien